An overview of radon concentration in Malaysia - Nisar Ahmad; Ihsan Ullah Khan; Jalil ur Rehman; Tabassum Nasir (Journal of Radiation Research and Applied Sciences, 2017)
It is known that the inhalation and ingestion of radon gas could lead to the primary health risks for lung and stomach cancers. Besides the health hazards of radon gas, it has different geological applications. In this context, numerous studies have been reported all over the world. Different research groups in Malaysia have also conducted and reported numerous studies since several decades. However, these studies are scattered and need to be compiled for future studies in Malaysia. The main emphasis is to overview and compiles these articles that will work as baseline data for the level of radon gas in Malaysia.